The use of antiviral drugs for influenza: Guidance for practitioners, 2012/2013; Paediatric summary - Allen, Upton D (Pulsus Group Inc, 2013)
This practice point summarizes the use of antiviral drugs to manage influenza illness in children and youth for the 2012/2013 season. It excerpts a recently published, full-length update of Canadian recommendations for clinicians on the use of antiviral drugs for the prevention and treatment of influenza, with a focus on paediatric antiviral therapy. Detailed information on the selective use of chemoprophylaxis can be found in the source document, which also highlights the importance of secondary bacterial infections (Streptococcus pneumoniae, methicillin-sensitive Staphylococcus aureus and methicillin-resistant S aureus) in cases of severe influenza illness.